KEARIFAN LOKAL SEBAGAI INSTRUMEN HUKUM DALAM PENGELOLAAN LINGKUNGAN HIDUP DI ERA INDUSTRIALISASI - Muhammad Amin; Nurul Amin; Fernandes Situngkir; Aullia Vivi Yulianingrum (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study analyzes the role and effectiveness of the local wisdom of Lubuk Larangan as a legal instrument in watershed management amid the expansion of industrial oil palm plantations, and examines strategies for harmonizing positive law with local law to support sustainable environmental governance. The research employs a normative juridical approach, analyzing statutory regulations, court decisions, and academic literature to assess the position of Lubuk Larangan as a living law. The findings indicate that Lubuk Larangan in Sumatra has effective normative binding power in river conservation, as reflected in better water quality and more sustainable fish populations. However, its implementation continues to face obstacles in the form of a gap between social recognition and formal state legal recognition, as well as the dominance of economic interests in oil palm plantation licensing (HGU) that overlap with customary river territories. This study offers a conceptual approach that positions Lubuk Larangan as a functional legal instrument and recommends a co-management model based on legal pluralism in watershed governance.